2011
DOI: 10.1111/j.1462-2920.2011.02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Microevolution of the major common Pseudomonas aeruginosa clones C and PA14 in cystic fibrosis lungs

Abstract: Clones C and PA14 are the worldwide most abundant clonal complexes in the Pseudomonas aeruginosa population. The microevolution of clones C and PA14 was investigated in serial cystic fibrosis (CF) airway isolates collected over 20 years since the onset of colonization. Intraclonal evolution in CF lungs was resolved by genome sequencing of first, intermediate and late isolates and subsequent multimarker SNP genotyping of the whole strain panel. Mapping of sequence reads onto the P. aeruginosa PA14 reference gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
166
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(177 citation statements)
references
References 43 publications
(55 reference statements)
9
166
1
1
Order By: Relevance
“…Finally, mutS, which encodes a mismatch repair protein (and which is responsible for the so-called "hypermutator" phenotype in some strains [20,23]), contained a nonsense mutation that truncated the encoded protein in both isolates from patient 7 at residue S813, leading to loss of the last 42 amino acids. To assess whether this truncation had functional consequences, we measured the rate of acquisition of spontaneous rifampin resistance (mainly due to rpoB mutations) for each isolate, as described by Cramer et al (3). The isolates from patients 5 and 6 all displayed negligible spontaneous Rif resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, mutS, which encodes a mismatch repair protein (and which is responsible for the so-called "hypermutator" phenotype in some strains [20,23]), contained a nonsense mutation that truncated the encoded protein in both isolates from patient 7 at residue S813, leading to loss of the last 42 amino acids. To assess whether this truncation had functional consequences, we measured the rate of acquisition of spontaneous rifampin resistance (mainly due to rpoB mutations) for each isolate, as described by Cramer et al (3). The isolates from patients 5 and 6 all displayed negligible spontaneous Rif resistance.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Cramer et al reported that patient "RN" accrued 15 SNPs over a period of ca. 15 years (no indels were reported [3]). Similarly, in the two longitudinal isolates sequenced by Smith et al (35), 41 SNPs and 27 indels appeared over a 7.5-year period.…”
Section: Discussionmentioning
confidence: 99%
“…This unusual strain also appears to have broad pathogenic ability, having been identified in infections of the urinary tract and peritoneal dialysis fluid [112]. Recently, sophisticated approaches, including genome sequencing, were used to study the evolution of both clone C and another abundant P. aeruginosa lineage (PA14), indicating differences between patients [113]. However, it is not clear whether the prevalence of such strain types in CF is attributable to transmissibility or merely a reflection of their environmental abundance.…”
Section: Other Uk Strainsmentioning
confidence: 99%
“…Evidence from longitudinal studies suggests that a large number of candidate genes can accrue substitutions during adaptation of P. aeruginosa (6)(7)(8)(9). Any given infection involves only a small subset of those substitutions, and most virulence-related phenotypes are not observed uniformly (10), making it difficult to say with confidence which genetic changes are most commonly associated with adaptation to the CF lung.…”
mentioning
confidence: 99%